Classroom Management in Industrial Settings and Industry-World of Work (IDUKA) in Enhancing Student Competence - Rusti Wulaningsih; Ahmad Yani T (CV. Publikasi Indonesia, 2024)
This research uses a qualitative approach with a case study method with techniques through observation, interviews, and documentation. The results of the study show that: 1) planning aspects have been carried out according to the conditions and abilities of the vocational school concerned, 2) programs in the implementation of cooperation have entered the criteria, 3) Expertise Competency Test (UKK) as a way of evaluation, students pass get skill competency certificate, and deserves to be distributed to work at IDUKA through the Vocational Special Job Exchange, 4) The problems faced are the unpreparedness of students to enter IDUKA, lack of student competence in productive fields, not seriousness of IDUKA, lack of funds for learning quality improvement programs, facilities and infrastructure that is not in accordance with IDUKA, as well as fees for guest teachers. Efforts made to deal with the problem are increasing teacher competence, mutually beneficial cooperation, building trust with IDUKA, and seeking donors from IDUKA. The conclusion of this study is that the management of industrial class SMK and IDUKA in improving student competence has been carried out in accordance with the provisions of standard operating procedures for industrial class management, in its implementation, it is very supportive of increasing student competence, although it is still not optimal due to limited support resources, both human resources and other resources. The need to build and improve collaboration with IDUKA is an absolute necessity for vocational high schools in improving student competence.